Future of Food : Shaping the Food System to Deliver Jobs - Townsend, Robert; Benfica, Rui Manuel; Prasann, Ashesh; Lee, Maria (World Bank, Washington, DC, 2017)
Shaping the Food System to Deliver Jobs is the fourth paper in a series on The Future of Food. This paper focuses on how the food system can deliver jobs. It provides a framework for understanding the factors determining the number and quality of jobs in the food system, including inclusion of women and youth. It highlights a set of actions that countries can adopt, adapt, and apply to their own circumstances to enhance the food system’s contribution to jobs. The food system extends beyond farm production to include food storage, processing, distribution, transport, retailing, restaurants and other services. The paper finds that the food system employs the most people in many developing countries in both self and wage employment, and will continue to do so for the foreseeable future. In many countries the off-farm aspect of the food system accounts for a large share of the economy’s manufacturing and services sectors. While the employment share in farming tends to decline as per capita incomes rise, the share in food manufacturing and services tends to increase. Urbanization and per capita income growth offers significant new opportunities in non-cereal products and in new jobs in the food system beyond the farm.